Phosphorus fractions in Cerrado Oxisols fertilized with liquid swine wastewater - Sulamirtes S. de A. Magalhães; Oscarlina L. dos S. Weber (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Knowledge of the forms of phosphorus (P) accumulation in soils that received successive applications of swine waste is essential to prevent the potential contamination risk of shallow waters. This study aimed to evaluate the forms of P accumulation in Cerrado Oxisols subjected to successive applications of liquid swine wastewater. Soil samples were collected from areas with and without use history of swine waste in the 0-0.10 and 0.10-0.20 m soil layers in Campo Verde and Nova Mutum, MT, Brazil. A sequential chemical fractionation was performed, determining the total and available P concentrations. The main forms of P accumulated in the 0-0.20 m layer, despite the soil texture and usage or not of swine wastewater, were residual P and moderately labile P. There was no predominance of more available P forms concerning the unavailable forms when comparing areas with and without the use of swine waste.